Simple microwave-assisted synthesis of carbon nanotubes using polyethylene as carbon precursor - Kure, N.; Hamidon, M. N.; Azhari, S.; Mamat, N. S.; Yusoff, H. M.; Isa, B. M.; Yunusa, Z. (Hindawi Publishing Corporation, 2017)
In this work, a quick and effective method to synthesize carbon nanotubes (CNTs) is reported; a commercial microwave oven of 600 W at 2.45 GHz was utilized to synthesize CNTs from plasma catalytic decomposition of polyethylene. Polyethylene and silicon substrate coated with iron (III) nitrate were placed in the reaction chamber to form the synthesis stock. The CNTs were synthesized at 750°C under atmospheric pressure of 0.81 mbar. Raman spectroscopy and field emission scanning electron microscope revealed the quality and entangled bundles of mixed CNTs from which the diameters of the CNTs were calculated to be between 1.03 and 25.00 nm. High resolution transmission electron microscope further showed that the CNTs obtained by this method are graphitized. Energy dispersive X-ray analysis and thermogravimetric analysis revealed above 98% carbon purity.